2021
DOI: 10.1128/mbio.02956-20
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1α (HIF1α) Suppresses Virus Replication in Human Cytomegalovirus Infection by Limiting Kynurenine Synthesis

Abstract: Human cytomegalovirus (HCMV) replication depends on the activities of several host regulators of metabolism. Hypoxia-inducible factor 1α (HIF1α) was previously proposed to support virus replication through its metabolic regulatory function. HIF1α protein levels rise in response to HCMV infection in nonhypoxic conditions, but its effect on HCMV replication was not investigated. We addressed the role of HIF1α in HCMV replication by generating primary human cells with HIF1α knocked out using CRISPR/Cas9. When HIF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Separately, our data show that cells lacking Hif1α are more permissive to infection ( Fig 4L ), suggesting Hif1α may play a role in limiting the initiation of infection. Consistent with this finding, Hif1α was recently shown to attenuate HCMV replication in human fibroblasts [ 46 ]. The anti-viral phenotype associated with Hif1α-mediated metabolic regulation is intriguing, yet the mechanisms responsible for TNFα-induced glycolysis still require elucidation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Separately, our data show that cells lacking Hif1α are more permissive to infection ( Fig 4L ), suggesting Hif1α may play a role in limiting the initiation of infection. Consistent with this finding, Hif1α was recently shown to attenuate HCMV replication in human fibroblasts [ 46 ]. The anti-viral phenotype associated with Hif1α-mediated metabolic regulation is intriguing, yet the mechanisms responsible for TNFα-induced glycolysis still require elucidation.…”
Section: Discussionsupporting
confidence: 75%
“…Kynurenine accumulates in a variety of inflammatory conditions and is induced during Human Immunodeficiency Virus (HIV) infection [ 47 , 48 ]. Others have described pro-viral effects of kynurenine on HCMV replication [ 46 ], suggesting a potentially complex relationship with infection that requires further analysis with respect to its roles in inflammation, intrinsic immunity and during viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway has previously been implicated in the immune response to CMV in studies of human cells and primary tissues 49,50 , suggesting this association may be a response to mammary CMV reactivation. Additionally, one study found that providing kynurenine to human fibroblasts promoted CMV replication, and blocking IDO1 decreased CMV replication 51 . Given our observational study design, we cannot determine if the association with increased IDO1/kynurenine is a cause or consequence of mammary CMV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact metabolic consequence remains unclear, the human immunodeficiency virus type 1 (HIV-1) viral protein Vpr induces stabilization of HIF-1α ( 117 ), resulting in the induction of two critical glycolytic enzymes, HK and PKM2 ( 118 ). In HCMV-infected cells, HIF-1α suppresses kynurenine levels and expression of the rate-limiting enzyme of kynurenine synthesis, indoleamine 2,3-dioxygenase 1 ( 119 ). HIF-1α reduces HCMV replication by regulating metabolism and metabolite signaling ( 119 ).…”
Section: Hypoxia-inducible Factor (Hif) Pathwaymentioning
confidence: 99%
“…In HCMV-infected cells, HIF-1α suppresses kynurenine levels and expression of the rate-limiting enzyme of kynurenine synthesis, indoleamine 2,3-dioxygenase 1 ( 119 ). HIF-1α reduces HCMV replication by regulating metabolism and metabolite signaling ( 119 ). Further studies remain necessary to identify viral factors required for HIF-1α induction during HCMV infection.…”
Section: Hypoxia-inducible Factor (Hif) Pathwaymentioning
confidence: 99%